Correction: Yue et al. YOLOv7-GCA: A Lightweight and High-Performance Model for Pepper Disease Detection. Agronomy 2024, 14, 618 - Xuejun Yue; Haifeng Li; Qingkui Song; Fanguo Zeng; Jianyu Zheng; Ziyu Ding; Gaobi Kang; Yulin Cai; Yongda Lin; Xiaowan Xu; Chaoran Yu (Agronomy, 2025)
In the original publication [...]